Application of Polya Strategy Assisted by Concrete Media to Improve Numeracy and Learning Outcomes in Elementary School Students - Rahmawati, Alfa Alfi; Indarini, Endang (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The background of this research is the low numeracy skills of students in solving problem-solving questions, the less attractive learning media used by the teacher and in the learning process, and the teacher's need to use the appropriate model/strategy in the learning process. This study aims to describe the implementation of the Polya Strategy assisted by concrete media to improve numeracy and student learning outcomes. Classroom Action Research (PTK) uses a model developed by Ernest T. Stranger, carried out during II actions. Each action has 3 stages, namely Look, Think, and Act. Researchers researched fifth-grade students at SD Pangudi Luhur Ambarawa with 37 students. This study's data collection techniques included interviews, observation, evaluation tests and documentation. The enumeration results of class V students at SD Pangudi Luhur Ambarawa in action I with a class average value of 70%, while action II achieved a class average of 86%. The learning outcomes of students in Action I with a class average value of 68%, while in Action II achieved a class average value of 80%.